A Multifactorial Analysis Of Association Between Cytokine Levels And Patients With Autoantibodies Anti-Ro/La From Northern Region Of Malaysia - Zubir, Anisah Abdul (2019)
Connective tissue diseases (CTDs) are one of the common autoimmune diseases (AIDs) in many countries and always associated with high levels of autoantibody anti-Ro and anti-La. The current study was conducted to determine the multifactorial analysis of association between pro- and anti- inflammatory cytokines, interleukin (IL)-6 & IL-10 respectively in sera of female positive anti-Ro or anti-La or both in northern Malaysia. Multiple factors including medication and menopause status were analyzed from samples diagnosed with CTD at different disease onset. Serum samples were collected from government hospitals in northern region Malaysia. Serum samples were screened for CTD using enzyme immunoassay (EIA). Presence of anti-nuclear antibody (ANA) patterns was tested by indirect immunofluorescence assay (IFA). Speckled IFA pattern was tested for anti-Ro and anti-La by EIA. Levels of IL-6 and IL-10 were measured using ELISA. Our findings showed that the mean age of positive anti-Ro or anti-La in female of Northern Malaysia was 38.1 years (SD±15.01) (n=106). Malay female represented the highest frequency of positive anti-Ro and anti-la autoantibodies compared to Chinese, Indian and other races in North Malaysia (72.6% vs. 17.0%, 7.5%, 2.8%). There are no significant associations between cytokine levels with medicines taken and hormonal status (p>0.05). However, result indicated that 97.4% of patients diagnosed with autoimmune-CTD were managed with steroid-based therapy.